The interaction effect of foreign capital inflows and financial development on economic welfare in sub-Saharan Africa - Kwame Acheampong (Financial Innovation, 2019)
This study examines the interaction effects of foreign capital inflows and financial development on economic welfare in sub-Saharan Africa (SSA). Estimates based on the system-GMM estimator using panel data on 23 SSA countries for 2000 to 2013 establish several results. First, the interaction between foreign capital inflows and financial development positively affects economic welfare in SSA. However, this effect was negative after one year. Second, the partial indirect effects of foreign capital inflows on economic welfare, conditional on the level of financial development, are positive, though they become negative after one year. Third, the total effect of foreign capital inflows on economic welfare is positive. The effect becomes negative after a year, though the predominant source of financial development is domestic credit. The consistency of these results indicates the importance of financial development in transmitting foreign capital to economic welfare enhancement. Developing the SSA's financial sector to meet specific welfare-enhancing demands may potentially convert a large share of capital inflows into improved economic welfare and eliminate the negative effects.
Keywords: D63; F30; G00; 650; Economic welfare enhancement; Foreign direct investment; Official creditors; Domestic credit; Money supply